Clinical characteristics and prognosis of paediatric respiratory syncytial virus-related encephalopathy - Yushan He; Gang Liu; Xiuwei Zhuo; Xiaojuan Tian; Jun Liu; Xiaomeng Xu; Suyun Qian (Italian Journal of Pediatrics, 2024)
Abstract Background To understand the clinical characteristics and prognosis of respiratory syncytial virus (RSV)-related encephalopathy in children. Methods A retrospective analysis of the data of children who were diagnosed with RSV-related encephalopathy and admitted to the paediatric intensive care unit (PICU) of Beijing Children’s Hospital between November 2016 and November 2023 was performed. Results Four hundred and sixty-four children with RSV infection were treated in the PICU, and eight of these patients (1.7%) were diagnosed with RSV-related encephalopathy. The mean age of the patients was 24.89 (5.92 ∼ 36.86) months. Two patients had underlying diseases. The time from the onset of illness to impaired consciousness was 3 (1.88–3.75) days. Five patients had convulsions, and three patients had an epileptic status. The serum procalcitonin (PCT) level was 1.63 (0.24, 39.85) ng/ml for the eight patients, and the cerebrospinal fluid (CSF) protein level was 232 (163 ∼ 848) g/L. Among the 8 patients, four patients underwent electroencephalogram (EEG) monitoring or examination. One patient showed continuous low-voltage, nonresponsive activity, and another patient displayed persistent slow waves, the remaining two patients had negative results. One patient had a combination of acute necrotizing encephalopathy (ANE) and acute encephalopathy with biphasic seizures and late reduced diffusion (AESD). Additionally, one patient had ANE, and another had acute brain swelling (ABS). One patient died in the hospital, and the other seven patients were discharged with improvement. Routine follow-up was conducted for 4.58(0.5 ∼ 6.50) years, and all patients fully recovered. Conclusions RSV-related encephalopathy could have varying clinical manifestations, and some types, such as ANE and ABS, are dangerous and can lead to death.